GENEAOLOGI KALENDER ISLAM JAWA MENURUT RONGGO WARSITO: Sebuah Komentar atas Sejarah Kalender dalam Serat Widya Pradhana - Ahmad Musonnif (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
Historians present the origin of the Javanese Islamic calendar by associating it with Sultan Agung. Ronggowarsito presented the history of Javanese-Islamic Calendar in different ways. In Widya Pradhana’s fiber, he did not mention the name of the Great Sultan in relation to the Javanese Calendar.Ronggowarsito actually associated the Islamic Calendar of Java with Sunan Giri II who lived long before the Sultan Agung. In addition, Ronggowarsito also wanted to explain the continuity of Islamic Arab calendar with the Islamic calendar of Java.